Once in the first times folk tales from the Philippines. - Sechrist, Elizabeth (Hough) 1903- (Macrae Smith Co., 1969)
A collection of fifty-one folktales from the Philippine Islands which tell of the animals, customs, and beliefs of the early Filipino people.